2022
DOI: 10.1186/s12894-022-01017-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for kidney stone disease recurrence: a comprehensive meta-analysis

Abstract: Background Kidney stone disease (KSD) is a common illness that causes an economic burden globally. It is easy for patients to relapse once they have suffered from this disease. The reported recurrence rate of KSD ranged from 6.1% to 66.9%. We performed this meta-analysis to identify various potential risk factors for the recurrence of KSD. Methods The PubMed, Embase and Web of Science databases were searched using suitable keywords from inception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 87 publications
(152 reference statements)
2
44
0
1
Order By: Relevance
“…Consistent with the findings of the two aforementioned studies [17,18] and in disagreement with the metaanalysis [16], we did not find a relationship between obesity and the recurrence rate of renal stones. However, in the univariate analysis conducted through the chi-squared test (χ2), a significant association (p < 0.05) was found between the recurrence rate and chronic diseases (more specifically, HTN), unilateral stones, and a stone diameter of 10-19 mm (1-1.9 cm).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the findings of the two aforementioned studies [17,18] and in disagreement with the metaanalysis [16], we did not find a relationship between obesity and the recurrence rate of renal stones. However, in the univariate analysis conducted through the chi-squared test (χ2), a significant association (p < 0.05) was found between the recurrence rate and chronic diseases (more specifically, HTN), unilateral stones, and a stone diameter of 10-19 mm (1-1.9 cm).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have found that having a previous history of the disease increases the recurrence of further episodes [ 15 ]. A meta-analysis of 53 articles and 488,130 enrolled patients, out of whom 17.4% experienced recurrence, found 12 demographic and clinical factors that increase the recurrence [ 16 ], including younger age, higher BMI, family history of renal stones, personal history of renal stones, hypertension, uric acid stone, being Caucasian, suspected renal stone episode before the first confirmed stone episode, the requirement for surgery, any concurrent asymptomatic (non-obstructing) stone, pelvic or lower pole kidney stone, and completion of 24-hour urine test.…”
Section: Discussionmentioning
confidence: 99%
“…In complicated KSD, extracorporeal shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PNL), ureteroscopy (URS) and other surgical procedures are the common therapeutic procedures to remove kidney stones [4] , [5] , [6] . Nevertheless, there is a high recurrence rate following the stone removal [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Nephrolithiasis is a rising problem globally, with the lifetime incidence having increased from 3% in the 1970s to 10% in Europe, 14% in North America and 20% in Saudi Arabia [ 1 ]. In parallel, the rate of stone recurrence has increased with almost 50% of stone patients experiencing an additional stone event within 5 years [ 2 ]. In the western world, both sexes are now almost equally affected.…”
Section: Introductionmentioning
confidence: 99%